Guidance on ambulatory blood pressure monitoring: A statement from the HOPE Asia Network - Kario, Kazuomi; Hoshide, Satoshi; Chia, Yook‐Chin; Buranakitjaroen, Peera; Siddique, Saulat; Shin, Jinho; Turana, Yuda; Park, Sungha; Tsoi, Kelvin; Chen, Chen‐Huan; Cheng, Hao‐Min; Fujiwara, Takeshi; et al. (The journal of clinical hypertension (Greenwich, Conn.), 2021)
Hypertension is an important public health issue due to its association with a number of serious diseases, including cardiovascular disease and stroke. The importance of evaluating hypertension taking into account different blood pressure (BP) profiles and BP variability (BPV) is increasingly being recognized, and is particularly relevant in Asian populations given the specific features of hypertension in the region (including greater salt sensitivity and a high rate of nocturnal hypertension). Ambulatory BP monitoring (ABPM) is the gold standard for diagnosing hypertension and assessing 24‐hour BP and provides data on several important parameters that cannot be obtained using any other form of BP measurement. In addition, ABPM parameters provide better information on cardio‐ and cerebrovascular risk than office BP. ABPM should be used in all patients with elevated BP, particularly those with unstable office or home BP, or who are suspected to have white‐coat or masked hypertension. ABPM is also an important part of hypertension diagnosis and monitoring in high‐risk patients. ABPM needs to be performed using a validated device and good practice techniques, and has a role both in hypertension diagnosis and in monitoring the response to antihypertensive therapy to ensure strict BP control throughout the 24‐hour period. Use of ABPM in clinical practice may be limited by cost and accessibility, and practical education of physicians and patients is essential. The ABPM evidence and practice points in this document are based on the Hypertension Cardiovascular Outcome Prevention and Evidence (HOPE) Asia Network expert panel consensus recommendations for ABPM in Asia. ABPM plays an important role in the diagnosis and management of hypertension, and is recognized as an essential part of good clinical practice in the field. The goal of the practice points provided is to help clinicians incorporate ABPM into their everyday practice to help improve patient outcomes.